Geodatabase and atlas: Karakalpakstan - Gafurov, Zafar; Eltazarov, Sarvarbek; Yuldashev, Tulkun; Djumaboev, Kakhramon; Zaitov, Sherzod; Kenjabaev, Shavkat (International Water Management Institute, 2024)
This product highlights the collaborative efforts undertaken to develop a comprehensive geodatabase and atlas for the Karakalpakstan. It encapsulates spatial data, analyses, and knowledge products aimed at addressing the challenges posed by arid climate conditions, water resource scarcity, and sustainable regional development. Utilizing modern tools like GIS, remote sensing, and climate modeling, this activity provides decision-makers with actionable insights for improving water use efficiency, land management, and ecological resilience in the region.